Rancang Bangun Monitoring Detak Jantung Pada Atlet Olahraga Futsal Berbasis Web Server - Muhamad Ibnu Roushul (CV. Multi Kreasi Media, 2022)
Futsal is a sport that is liked by many people, but it is necessary to pay attention to when exercising, especially for a futsal athlete during cardio training because when exercising, the heart rate will increase which is quite important. This condition occurs because the heart is working extra pumping blood to the muscles, so it can get nutrients and oxygen intake to continue exercising. To know the limit of normal heart rate during exercise is very important. If the heart rate exceeds the normal limit, this condition can trigger various health problems. In this study, the authors designed a tool to monitor heart conditions using a Heart Rate sensor in futsal athletes based on a web server with Wemos D1 Mini. The goal is for the mentor or coach to know information about the condition of the athlete's heart rate during field training. In the design, the author has determined that the normal heart rate before activity is heart rate < 100 with low bpm status then during activities, namely 100 < 170 with normal bpm status and heart rate > 170 with high bpm status.